Comparison of recording of hepatitis B infection in the NSW Perinatal Data Collection with linked hepatitis B notifications - Lucy Deng; Joanne Reekie; Andrew Hayen; Marlene Kong; John M Kaldor; James Ward; Bette Liu (Sax Institute, 2017)
Objective: Results of routine maternal antenatal hepatitis B (HBV) screening have been recorded in the New South Wales (NSW) Perinatal Data Collection (PDC) since January 2011. We evaluated the accuracy of this reporting in 2012, the first year that comprehensive data were available, by linking the PDC to HBV notifications. Methods: PDC records of mothers giving birth in 2012 were probabilistically linked to HBV notifications recorded in the NSW Notifiable Conditions Information Management System (NCIMS). Sensitivity and specificity of the PDC record of HBV status were determined using a linked HBV notification from the NCIMS database as the gold standard. Results were also examined according to health service (area health service, hospital level, public or private) and individual factors (maternal age, country of birth, Aboriginality, parity, timing of first antenatal visit). Results: Among 99 510 records of women giving birth in NSW in 2012, positive HBV status was recorded for 0.69% of the women according to the PDC record and 0.90% from linked NCIMS records. The overall sensitivity of the HBV status variable in the PDC data was 65.5% (95% confidence interval [CI] 62.4, 68.7) and positive predictive value was 85.3% (95% CI 82.6, 87.9). In general, the low prevalence of HBV meant we had limited statistical power to assess differences between health service factors and maternal factors; however, sensitivity was significantly lower in PDC data for HBV in Australian-born non-Aboriginal women (37.0%; 95% CI 27.5, 46.7) than in overseas-born women (69.9%; 95% CI 66.6, 73.1; p < 0.001). Conclusions: PDC records of HBV status for women giving birth in 2012 had high specificity but poor sensitivity. Sensitivity varied across area health services and levels of maternal services, and by various maternal factors. Because the results of maternal HBV screening can be used to monitor HBV prevalence in adults, analysis of the PDC records in subsequent years is necessary to track whether sensitivity improves over time.